Influence of technology addiction, psychosocial risk factors, technostress, and self-control on the psychological well-being of university students in Pakistan - Bajwa, Ruqia Safdar (2022)
Technology now reaches deep into our psyches and lives. Excessive technology use impacts human development and social functioning, and constant interaction with technology compromises psychological well-being. Previous empirical findings on the relationship between technology-related behaviors and psychological well-being are diverse and not explored. Based on the theoretical assumptions of Ryff's theory of Psychological Well-being and the Person-Technology Fit Model, the current correlational study determines the relationship between technology addiction (problematic internet use, smartphone addiction), psychosocial risk factors (phubbing, fear of missing out, loneliness, social phobia/anxiety, and social comparison), technostress, self-control, and psychological well-being among university students in Pakistan. It also investigates the direct effects of technology addiction and psychosocial risk factors on psychological well-being, the mediating role of technostress in the relationship between technology addiction, psychosocial risk factors, and psychological well-being, and the moderating effect of self-control on the relationship between technostress and psychological well-being. The study uses a multistage cluster random sampling method to collect data from two public sector universities in south Punjab, Pakistan. It involves 866 university students. The study administers a Problematic Internet Use Questionnaire, Smartphone Addiction Scale, Phubbing Scale, Fear of Missing Out Scale, Three-Item Loneliness Scale, Mini-Social Phobia Inventory, Scale for Social Comparison Orientation, Technostress Questionnaire, Brief Self-Control Scale, and Ryff's Psychological Well-Being Scale among the respondents through a web link in the virtual classrooms. The results showed that problematic internet use, smartphone addiction, fear of missing out, loneliness, and social comparison were significantly associated with psychological well-being. In contrast, phubbing and social phobia/anxiety were not mainly related to psychological well-being. Structural equation modeling demonstrated that technostress partially mediated the relationship between problematic internet use, smartphone addiction, fear of missing out, loneliness, and psychological well-being. In contrast, technostress fully mediated the relationship between social phobia/anxiety and psychological well-being. Nonetheless, it failed to function as a significant mediator in the relationship between phubbing and psychological well-being. Besides, self-control significantly moderated the relationship between technostress and psychological well-being. The current study highlighted the virtual social world's dynamics that considerably affect university students' psychological well-being. The present study provides valuable insights regarding the impact of technology addiction and its related psychosocial factors on psychological well-being and how self-control mitigates technostress. This study substantially contributed to the existing knowledge based on solid theoretical reasoning and enough empirical support. Current findings show significant implications for the field of study, theory, methodology, and policymakers.